(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article provides information on the emergence of the Jadid movement, known as a socio-political and educational movement that emerged in Turkestan at the end of the last century, the main goal of the movement, and the role of Is’hoqkhan tora Ibrat, one of the major representatives of the Turkestan Jadid movement, in the development of the Jadid movement.